Cross-sectional survey describing general practitioners' absolute cardiovascular disease risk assessment practices and their relationship to knowledge, attitudes and beliefs about cardiovascular disease risk in Queensland, Australia. Issue 8 (13th August 2020) - Greaves, Kim; Smith, Anita; Agostino, Jason; Kunarajah, Kuhan; Stanton, Tony; Korda, Rosemary
Abstract : Objectives: To describe general practitioners' (GPs') absolute cardiovascular disease risk (ACVDR) self-reported assessment practices and their relationship to knowledge, attitudes and beliefs about ACVDR. Design: Cross-sectional survey with opportunistic sampling (October–December 2017). Setting: Sunshine Coast region, Queensland, Australia. Participants: 111 GPs responded to the survey. Primary and secondary outcome measures: Proportion of GPs reporting a high (≥80%) versus moderate (60%–79%)/low (<60%) percentage of eligible patients receiving ACVDR assessment; proportion agreeing with statements pertaining to knowledge, attitudes and beliefs about ACVDR and associations between these factors. Results: Of the 111 respondents, 78% reported using the Australian ACVDR calculator; 45% reported high, 25% moderate and 30% low ACVDR assessment rates; >85% reported knowing how to use ACVDR assessment tools, believed assessment valuable and were comfortable with providing guideline-recommended treatment. Around half believed patients understood the concept of high risk and were willing to adopt recommendations. High assessment rates (vs moderate/low) were less likely among older GPs (≥45 vs ≤34 years, age-adjusted and sex-adjusted OR (aOR) 0.36, 95% CI 0.12 to 0.97). Those who answered knowledge-based questions about the guidelines incorrectly had lower assessment rates, including those who answered questions on patient eligibility (aOR 0.13, 95% CI 0.02 to 1.11). A high assessment rate was more likely among GPs who believed there was sufficient time to do the assessment (aOR 3.79, 95% CI 1.23 to 11.61) and that their patients were willing to undertake lifestyle modification (aOR 2.29, 95% CI 1.02 to 5.15). Over 75% of GPs agreed better patient education, nurse-led assessment and computer-reminder prompts would enable higher assessment rates. Conclusions: Although the majority of GPs report using the ACVDR calculator when undertaking a CVD risk assessment, there is a need to increase the actual proportion of eligible patients undergoing ACVDR assessment. This may be achieved by improving GP assessment practices such as GP and patient knowledge of CVD risk, providing sufficient time and nurse-led assessment.